Development of Classpoint Assisted Food Chain Learning Media to Improve Student Learning Outcomes in Elementary Schools - Sarah, Siti; Ali, Enjang Yusuf; Ismail, Ali (LJPI UI Bunga Bangsa Cirebon, 2024)
This study aims to develop interactive learning media using the Classpoint application to improve the learning outcomes of fifth-graders in science lessons in elementary schools. The study employed a research and development (R&D) method with a 4D model. The resulting product is a media that can be used by both teachers and students, which contains various features, ranging from material to quizzes to train students' knowledge abilities. This media is run by teachers using laptops/computers and students can use it using their mobile phones without the need to download an application. The research design used is a non-experimental one-group pretest-posttest design by comparing learning outcomes before (pretest) and after using the Classpoint-assisted interactive learning media (posttest). The Classpoint-assisted interactive learning media has been validated by media experts with a percentage of 87.5%, material experts with 97.2%, and language experts with 95%, with an overall average of 91.5% and a category of